The Coronary Arteries in Adults after the Arterial Switch Operation: A Systematic Review - Leo J. Engele (Journal of Cardiovascular Development and Disease, 2021)
Coronary artery status in adults long after the arterial switch operation (ASO) is unclear. We conducted a systematic review to provide an overview of coronary complications during adulthood and to evaluate the value of routine coronary imaging in adults after ASO, in light of current guidelines. Articles were screened for the inclusion of adult ASO patients and data on coronary complications and findings of coronary imaging were collected. A total of 993 adults were followed with a median available follow-up of only 2.0 years after reaching adulthood. Myocardial ischemia was suspected in 17/192 patients (8.9%). The number of coronary interventions was four (0.4%), and coronary death was reported in four (0.4%) patients. A lack of ischemia-related symptoms cannot be excluded because innervation studies indicated deficient cardiac innervation after ASO, although data is limited. Anatomical high-risk features found by routine coronary computed tomography (cCT) included stenosis (4%), acute angle (40%), kinking (24%) and inter-arterial course (11%). No coronary complications were reported during pregnancy (n = 45), although, remarkably, four (9%) patients developed heart failure. The 2020 European Society of Cardiology (ESC) guidelines state that routine screening for coronary pathologies is questionable. Based on current findings and in line with the 2018 American ACC/AHA guidelines a baseline assessment of the coronary arteries in all ASO adults seems justifiable. Thereafter, an individualized coronary follow-up strategy is advisable at least until significant duration of follow-up is available.